2017
DOI: 10.1177/0032321717722360
|View full text |Cite
|
Sign up to set email alerts
|

Impartiality and the Definition of Corruption

Abstract: The study of political corruption has been beset by disagreements concerning the exact definition of the term. One definition that has grown increasingly popular in the social-scientific literature in recent years is that proposed by Oskar Kurer and developed by Bo Rothstein: political corruption should be understood as a breach of the norm of impartiality. This article argues that while this definition has intuitive plausibility and while its relative parsimony makes it attractive for cross-cultural social-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
8
1
1
Order By: Relevance
“…In our 2018 article (and a previous working paper [Marquette & Peiffer, ]), we reviewed the literature on corruption and collective action—including, but not limited to Persson et al (). Contrary to our original expectations, we found that while the arguments put forward by Persson et al had “intuitive plausibility,” to quote Sparling (), unpacking the theory and its application revealed important challenges with regard to both the theory as posited and its potential application in practice. While far from dismissing the ideas put forward by Persson et al and others, in our article we nonetheless found that (a) the case against principal–agent theory had not been proven and that there was a risk of throwing the baby out with the bathwater; (b) that the application of collective action theory was incomplete [which Persson et al (, p. 3) acknowledge, though they do not explain why or offer a solution]; and (c) that when “the benefits of passively or actively engaging in corrupt activities seem to outweigh the costs” (Persson et al, , p. 463), the most important question to follow, surely, is why ?…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…In our 2018 article (and a previous working paper [Marquette & Peiffer, ]), we reviewed the literature on corruption and collective action—including, but not limited to Persson et al (). Contrary to our original expectations, we found that while the arguments put forward by Persson et al had “intuitive plausibility,” to quote Sparling (), unpacking the theory and its application revealed important challenges with regard to both the theory as posited and its potential application in practice. While far from dismissing the ideas put forward by Persson et al and others, in our article we nonetheless found that (a) the case against principal–agent theory had not been proven and that there was a risk of throwing the baby out with the bathwater; (b) that the application of collective action theory was incomplete [which Persson et al (, p. 3) acknowledge, though they do not explain why or offer a solution]; and (c) that when “the benefits of passively or actively engaging in corrupt activities seem to outweigh the costs” (Persson et al, , p. 463), the most important question to follow, surely, is why ?…”
contrasting
confidence: 97%
“…While we do not have the space to address this in full here, there are recent critiques regarding this vision of universalism/impartiality. For example, Sparling (, p. 378) argues that: “it is, indeed, a dangerous ideal if transformed into the touchstone of good government precisely because it attempts to depoliticise debates about corruption.” Heywood (, p. 86) says that this vision of impartiality “has little to say about how to address genuine ethical dilemmas or challenges that, for some, represent the only true test of whether individuals act with integrity.”…”
mentioning
confidence: 99%
“…Corruption is understood as a standard of behavior that deviates from the prevailing norms in a given context under a particular motivation, that is, private gain at the expense of public gain (Rodrigues & Barros, 2020). With regard to the political perspective, Sparling (2018) believes that corruption should be perceived as a violation of the norm of impartiality. Impartiality, therefore, must be understood as a normative exemption procedure resulting from a sense of fairness that exists among stakeholders.…”
Section: Perception Of Corruptionmentioning
confidence: 99%
“…Second, assuming that corruption automatically violates the principle of impartiality is problematic because if corrupt politicians are equally corrupt with every citizen, then they are not partial (Sparling, 2018). Instead, we adopt the World Bank's influential definition of governance as 'the traditions and institutions by which authority is exercised.…”
Section: Qog and Erps Political Normalisationmentioning
confidence: 99%